Conventional surgery and transcatheter closure via surgical transapical approach for paravalvular leak repair in high-risk patients: results from a single-centre experience. - Taramasso,M; Maisano,F; Latib,A; Denti,P; Guidotti,A; Sticchi,A; Panoulas,V; Giustino,G; Pozzoli,A; Buzzatti,N; Cota,L; De,Bonis M; et al. (Eur Heart J Cardiovasc Imaging, 2014)
OBJECTIVES: Paravalvular leaks (PVL) occur in up to 17% of all surgically implanted prosthetic valves. Re-operation is associated with high morbidity and mortality. Transcatheter closure via a surgical transapical approach (TAp) is an emerging alternative for selected high-risk patients with PVL. The aim of this study was to compare the in-hospital outcomes of patients who underwent surgery and TA-closure for PVL in our single-centre experience. METHODS: From October 2000 to June 2013, 139 patients with PVL were treated in our Institution. All the TA procedures were performed under general anaesthesia in a hybrid operative room: in all but one case an Amplatzer Vascular Plug III device was utilized. RESULTS: Hundred and thirty-nine patients with PVL were treated: 122 patients (87.3%) underwent surgical treatment (68% mitral PVL; 32% aortic PVL) and 17 patients (12.2%) underwent a transcatheter closure via a surgical TAp approach (all the patients had mitral PVL; one case had combined mitral and aortic PVLs); in 35% of surgical patients and in 47% of TAp patients, multiple PVLs were present. The mean age was 62.5 ± 11 years; the Logistic EuroScore was 15.4 ± 3. Most of the patients were in New York Heart Association (NYHA) functional class III-IV (57%). Symptomatic haemolysis was present in 35% of the patients, and it was particularly frequent in the TAp (70%). Many patients had >1 previous cardiac operation (46% overall and 82% of TAp patients were at their second of re-operation). Acute procedural success was 98%. In-hospital mortality was 9.3%; no in-hospital deaths occurred in patients treated through a TAp approach. All the patients had less than moderate residual valve regurgitation after the procedure. Surgical treatment was identified as a risk factor for in-hospital death at univariate analysis (OR: 8, 95% CI: 1.8-13; P = 0.05). Overall actuarial survival at follow-up was 39.8 ± 7% at 12 years and it was reduced in patients who had &g